Analysis of Guru Penggerak Programs as Sustainable Professional Development for Teachers - Safrizal Safrizal; Nurhafizah Nurhafizah; Resti Yulia; Husnani Husnani (STAI Hubbulwathan Duri, 2022)
The problem of teacher competence is still a classic that occurs at the level of teacher competency test results which are still below the minimum provincial average set. This situation becomes the focus of the problem that needs to be found a way out. One of them is the driving teacher program launched by the Minister of Education and Culture. The purpose of this study was to analyze the concept and content of the implementation of driving teachers as a means of continuous professional development. This study uses a qualitative approach. Research informants were selected by the purposive sampling technique. The data collection process was carried out by in-depth interviews, documentation studies, and field notes. Data analysis was carried out by referring to the Miles and Huberman model. To ensure the validity of the data, researchers used triangulation techniques and increased the persistence of researchers in analyzing the documents found. The results show that the concept of guru penggerak program is directed so that teachers can become leaders, instructors, and motivators for their colleagues by providing training content in the form of activities that encourage the birth of a positive community that not only provides up-to-date information but also provides experience in solving learning problems. naturally, so that this becomes a valuable experience for the teacher. so that the guru penggerak program can be a means of developing teachers' social competence, but also allows them to develop their professional abilities.